APPLICATION OF GMP AND SSOP IN BALINESE TRADITIONAL FOOD SAFETY 'PEDETAN' SARDINE FISH (Sardinella Sardine Bleeker) - ayu suardani; putu candra; A.A. made semariyani (UNEJ e-Proceeding, 2017)
Sardine Processing Industry 'Pedetan' is one of the traditional Balinese Processing Industry conducted by the people of Jembrana Regency in Bali. The community cultivates Sardine fish with low sanitation and hygiene and unsafe food security levels. Technology processing and management are still very simple. This study aims to analyze the quality and safety of Sardine associated with the application of GMP and SSOP in an effort to produce quality and safe traditional food consumed. Research is done by analyzing GMP and SSOP which have been done by the manufacturer and make the model of application of GMP and SSOP in processing process. Test Model of GMP and SSOP implementation that has been implemented to produce the product of Sardine fish that according to SNI 8273-2016 standard on Quality Requirement and Safety of dried salted fish, including moisture content, salt content, acid soluble ash content, microbial contamination including Total Plate Count, Escherichia coli, and sensory.